Terrorism-Related Topic In The Language Of Fake News In Indonesia - Ahmet Yiğitalp Tulga; Tonny Dian Effendi (Mandala: Jurnal Ilmu Hubungan Internasional, 2022)
The discussion on the relations between terrorism and social media mainly focuses on social media's role in spreading the terrorism ideology and recruiting the member of the terrorist group. However, social media has also become means to share fake news related to terrorism. Considering the relationship between fake news and terrorism, the primary purpose of this study is to examine the content, language used, and emotion of fake news about terrorism in Indonesia. It also reveal what kind of language used in fake news to manipulate the public and what emotions it appeals to. We analyzed fake news about terrorism in Indonesia using quantitative text analysis methods, such as sentiment analysis and dictionary-based analysis methods with R statistical software. We created two dictionaries covering the religious and violence words, and fake news was examined under these two dictionaries. For reliability, we applied the "Split-half test" to the results and we reached similar results. This study shows that ISIS, Aceh, and terrorist action in Sulawesi are three dominant topics in fake news. Second, the language on fake news is mostly about terrorism and violence to create fear in society. Third, violence and religious language are equal in the language of misleading content. We interpreted the results obtained with the traditional fear of crime theory. We then discussed the major results of this research and made effort to explain reasons behind our research results. The study has a limitation because of the small number of fake news. Future studies may overcome this limitation by selecting multiple countries as cases or increasing the date range of fake news. The dictionary-based method we used in this study is relatively new for the literature and provides the opportunity to analyze fake news content effectively. Our results using the Dictionary-based method can provide valuable clues for policymakers in the counter-terrorism field.